Co‐production, governance and practice: The dynamics and effects of User Voice Prison Councils. (5th September 2018) - Weaver, Beth
Abstract: Drawing on Bevir's (2013) decentered theory of governance, and Donati's (2016) theory of the relational subject, this article explores how User Voice Prison Councils in England have contributed to shifts in aspects of prison governance and practice. It discusses the cultural and policy context in which the Councils emerged and operate before exploring their perceived purposes, dynamics, and effects. User Voice Prison Councils represent an important example of different actors co‐producing alternative patterns of governance through innovations in democratic participation. Interviews with Prison Council participants, User Voice and prison staff revealed that the development of such "bottom–up" participatory governance practices require and restore interpersonal trust, the mechanisms of which are interactions underpinned by a distinct manner of relating and the establishment of a network of relations oriented to the common good. The effects include enhanced institutional legitimacy; improvements in prison officer‐prisoner relations; and greater quality of life for prisoners. Revealing the "how" of co‐production, from the "inside", the argument advanced here is that while the effects of co‐production may be more ameliorative than transformative, such collaborative and dialogic approaches can enable differently situated people to forge new norms of interactions and forms of democratic participation to achieve collective goals.